The Conflicting Traditions of Portraying the Jewish People in the Chester Mystery Cycle - Matyjaszczyk, Joanna (Text Matters: A Journal of Literature, Theory and Culture, 2018)
The article seeks to analyze the portrayal of the Jews in two plays from the Chester mystery cycle: “Trial and Flagellation” and “The Passion.” The analysis acknowledges that the cycle is a mixture of, and a dialogue between, the universal standpoint emerging from the presentation of the biblical story of humankind and a contemporary perspective, pertaining to the reality of the viewers. Therefore, while pointing to the unique formal and structural uniformity of the cycle, which strengthens the idea of continuity between the Old and the New Covenant and the role of the Israelites in the history of salvation, it also recognizes the potential of the plays to engage in the current stereotypes. The article examines how the Gospel account of Christ’s trial and death is modified through presenting the Jews as torturers, whitewashing the non-Jewish characters, and placing special emphasis on the question of Jewish ignorance. It is demonstrated how different theological and popular stances concerning the Jewish people are merged and reconciled in the Chester representation of the passion of Christ and it is argued that the plays in question retell the biblical story in such a way that the justification for the expulsion of the Jews from England could be derived from it.